Pour une écriture écologique dans le diptyque Rue des Perplexes et Quand passent les âmes errantes du romancier algérien Mohamed Magani - Malki Benaid (Carnets)
We live in the era of the Anthropocene, a concept brought up to date by environmental humanities to mean that man is no longer "the measure and the center of all things," as Protagoras advocated, but an element, decisive as it is, and, above all, formidable, of a vast biotope. Indeed, while the other elements of this system functioned spontaneously in harmony, the misplaced behaviors of Homos sapiens, from the Neolithic to the contemporary era, have disrupted, and forever altered, the balance of this symbiotic system: climate warming due to greenhouse gas emissions, depletion of natural resources caused by overexploitation, and the gradual extermination of wildlife and flora. Ipso facto, it has become evident that humans are merely beings situated in the world, living among other living beings, and no longer the "privileged" entities of the past, as they believed themselves to be at the center of the world and at the top of pyramid of life due to their logos and intelligence. In such a situation of vulnerability, alarm bells have already been sounded, and environmental issues have emerged as central themes in contemporary artistic reflection, particularly in literary thought, where they assert themselves as predominant discursive schemes. Ipso facto, literature engages, in its own way, in the ecological struggle with the means at its disposal. To illustrate the ecocentric orientation of contemporary writing, we have chosen to approach the diptych Rue des Perplexes and Quand passent les âmes errantes, by Mohamed Magani from the perspective of a dual ecopoetic and zoopoetic reading. The iconoclast Algerian author in question has indeed dared to venture onto the still virgin territory of environmental writing in Algeria.